1987
DOI: 10.1177/002221948702000204
|View full text |Cite
|
Sign up to set email alerts
|

Making Decisions About Special Education Placement: Do Low-Income Parents Have the Information They Need?

Abstract: Using the hypotheses-generating techniques ofGlaser and Strauss (1967), interviews were conducted with 35 low-income parents in an attempt to ascertain their knowledge of and their feelings about the adequacy of schooling in general and special education services in particular. Thirty-six percent of the respondents had school-aged children who were receiving special education services. The majority of parents had positive feelings about special education, although parents of learning disabled students perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…In a national survey of Native American parents of children referred to special education, Robinson-Zanartu and Majel-Dixon (1996) found that parents experienced difficulty understanding evaluation, intervention, and placement processes. Brantlinger (1987), in her study of low-income parents of children receiving special education services, found that many parents were confused about the classification system, placement and service options, and concepts such as due process, least restrictive environment, and mainstreaming. Thus, evidence from special education and public health studies suggests that literacy-related skills and demands may influence the ability of the parent or caregiver to advocate on behalf of his or her child with a disability within multiple service settings.…”
Section: Discussionmentioning
confidence: 99%
“…In a national survey of Native American parents of children referred to special education, Robinson-Zanartu and Majel-Dixon (1996) found that parents experienced difficulty understanding evaluation, intervention, and placement processes. Brantlinger (1987), in her study of low-income parents of children receiving special education services, found that many parents were confused about the classification system, placement and service options, and concepts such as due process, least restrictive environment, and mainstreaming. Thus, evidence from special education and public health studies suggests that literacy-related skills and demands may influence the ability of the parent or caregiver to advocate on behalf of his or her child with a disability within multiple service settings.…”
Section: Discussionmentioning
confidence: 99%
“…The gender difference observed in this study thus may be reduced by improving access to health information for men. In addition, since income is closely associated with accessibility of information (Brantlinger 1987), it may explain why income is only significant for women since as discussed above, women are more active in health information seeking.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of what consenting parents may have been told (Brantlinger, 1986), some classification is not intended to benefit those labeled. McGill-Franzen and Allington (1993) describe how, in response to pressures on administrators to have their districts look good on high-stakes tests, some students are classified so their scores are not included in the test pool and the districts' aggregate test results appear better to the public.…”
Section: Disabling Practicementioning
confidence: 99%
“…Subordinates internalize messages about their own inferiority (Brantlinger, 1993) and are persuaded that differentiating and stigmatizing programs are in their own best interests (Brantlinger, 1986), so these forms of symbolic violence take place with their consent, however reluctant and resented. Thus, not only are "the dominant dominated by their domination," as Bourdieu (1998) cites Marx as having said, but because of their submission to unfair practice and their deference to professional authority, those dominated contribute to their own domination.…”
Section: Disabling Practicementioning
confidence: 99%